Repeated cross-sectional sero-monitoring of SARS-CoV-2 in New York City - Stadlbauer, Daniel; Tan, Jessica; Jiang, Kaijun; Hernandez, Matthew M.; Fabre, Shelcie; Amanat, Fatima; Teo, Catherine; Arunkumar, Guha Asthagiri; McMahon, Meagan; Capuano, Christina; Twyman, Kathryn; Jhang, Jeffrey; et al. (Nature (London), 2021)
In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first detected in China and has since caused a pandemic of coronavirus disease 2019 (COVID-19). The first case of COVID-19 in New York City was officially confirmed on 1 March 2020 followed by a severe local epidemic 1 . Here, to understand seroprevalence dynamics, we conduct a retrospective, repeated cross-sectional analysis of anti-SARS-CoV-2 spike antibodies in weekly intervals from the beginning of February to July 2020 using more than 10,000 plasma samples from patients at Mount Sinai Hospital in New York City. We describe the dynamics of seroprevalence in an ‘urgent care’ group, which is enriched in cases of COVID-19 during the epidemic, and a ‘routine care’ group, which more closely represents the general population. Seroprevalence increased at different rates in both groups; seropositive samples were found as early as mid-February, and levelled out at slightly above 20% in both groups after the epidemic wave subsided by the end of May. From May to July, seroprevalence remained stable, suggesting lasting antibody levels in the population. Our data suggest that SARS-CoV-2 was introduced in New York City earlier than previously documented and describe the dynamics of seroconversion over the full course of the first wave of the pandemic in a major metropolitan area. Seropositive samples of SARS-CoV-2 were detected as early as mid-February in patients at Mount Sinai Hospital in New York City, and antibody positivity increased during the first wave of the pandemic and remained stable afterwards.